Standardization and clinical applicability of sensori-neural acuity level test - Mary John (Journal of All India Institute of Speech and Hearing)
Bone conduction testing is one of the most important tests in hearing evaluation. In the differential diagnosis of hearing impairment, the measurement of pure tone bone conduction thresholds is sought as a primary means of establishing the existence and amount of sensorineural component of the hearing loss. The testing by bone conduction became extensive in clinical procedures after Wheatstone in 1827. Clinical air conduction and Bone conduction thresholds are used primarily to ascertain the presence or absence of an external or middle ear lesion and to determine quantitatively the magnitude of the conductive hearing impairment